A study on employee engagement and organizational performance of knit wear industry in tirupur district - Gopalan, Visuanathan; Clifford Joe, C. Gladson (International Journal of Psychosocial Rehabilitation, 2020)
Employee engagement is a work associated aspect of employees and it may be featured by enthusiasm, dynamism and assimilation of employees and it enhances production and performance of organizations and it may be attained through emotions and commitments of employees. Employees are agreed with they sense exploding with energy in their work, they are very strong and energetic in their work, they are enthusiastically doing their work, they are proud of their work, time is moving fast when they are performing their work, they are fully involved in their work and they are doing their work meaningfully. Significant difference is there amongst employee engagement in knit wear industry and profile of employees. Employee engagement of employees has significant, positive and moderate relation with organizational performance of knit wear industry. Hence, employees should get inspiration from their work and they must be happy when they are intensely doing their work. Besides, employees should not feel that their work is challenging to them and thy must take necessary measures to solve issues related to their work.